Notice of Retraction Intermittently Connected Cloudlet System to Obtain an Optimal Offloading Policy - Nadim Akhtar; N. Srinivasan (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2016)
Notice of Retraction-----------------------------------------------------------------------After careful and considered review of the content of this paper by a duly constituted expert committee, this paper has been found to be in violation of IAES's Publication Principles.We hereby retract the content of this paper. Reasonable effort should be made to remove all past references to this paper.The presenting author of this paper has the option to appeal this decision by contacting ijeei.iaes@gmail.com.-----------------------------------------------------------------------The great potential has been shown over the performance enhancement for offloading the mobile devices within intensive parts of computation within mobile cloud application. The complete realization for the potential which being mismatch within the particular mobile devices on the resource computing demand and that provide an offer. The request over offloading is connecting the variable network where cloud services are always being in the required process within infrequent, variable connectivity of network and quick response time for relatively incurring the times for long setup and quanta for long time are may be indifferent for the connectivity of network. The requirement over the mobile application is needed more resources for executing the single device task within the fact of mobile devices enhanced capabilities. The problems have been addressed for several computation of offloading the remote cloud services and resources which is locating the computing resources in the cloudlets. The proposed concept is proposing an experimental approach for highlighting the tradeoff of offloading. The proposed architecture of the generic algorithm is performing an integration of mobile cloud computing for automatic offloading to improve the application response time when minimizing the consumption of energy for mobile device. Offloading task within a remote machine is not better than performing task particularly. The particular performance of the task is always better than remote machine. The proposed system is developing an algorithm of optimal offloading for mobile user which considering over the cloudlets availability and local load of user’s. The solution and formulation of the MDP (Markov Decision Process) model is for obtaining a policy to the user mobile and minimizing the objective of offloading cost and computation cost.